2012
DOI: 10.1007/978-94-007-2888-2_40
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Calcium Signaling

Abstract: The increasing interest in stem cell research is linked to the promise of developing treatments for many lifethreatening, debilitating diseases, and for cell replacement therapies. However, performing these therapeutic innovations with safety will only be possible when an accurate knowledge about the molecular signals that promote the desired cell fate is reached. Among these signals are transient changes in intracellular Ca2+ concentration [Ca2+]i. Acting as an intracellular messenger, Ca2+ has a key role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 123 publications
3
94
0
2
Order By: Relevance
“…These results indicate that both nAChR subtypes are likely involved in SCO generation and that there is a differential modulation of nAChRs on the frequency and amplitude of SCO. The differential modulation of nAChR subtypes on the frequency and amplitude of [Ca 2ϩ ] i oscillations supported the notion that the frequency and amplitude of [Ca 2ϩ ] i oscillations encode different information contained in the Ca 2ϩ signal (2,29). Albeit the different effects of DH␤E on the frequency and amplitude of SCO, DH␤E pretreatment prevented the nicotinic increment of frequency and the amplitude of [Ca 2ϩ ] i oscillations, suggesting that ␣ 4 ␤ 2 -nAChRs play a critical role in both SCO and NCO.…”
Section: Discussionsupporting
confidence: 57%
“…These results indicate that both nAChR subtypes are likely involved in SCO generation and that there is a differential modulation of nAChRs on the frequency and amplitude of SCO. The differential modulation of nAChR subtypes on the frequency and amplitude of [Ca 2ϩ ] i oscillations supported the notion that the frequency and amplitude of [Ca 2ϩ ] i oscillations encode different information contained in the Ca 2ϩ signal (2,29). Albeit the different effects of DH␤E on the frequency and amplitude of SCO, DH␤E pretreatment prevented the nicotinic increment of frequency and the amplitude of [Ca 2ϩ ] i oscillations, suggesting that ␣ 4 ␤ 2 -nAChRs play a critical role in both SCO and NCO.…”
Section: Discussionsupporting
confidence: 57%
“…Hence, we wondered whether ion channels could be involved in transducing matrix mechanical cues to intracellular signaling pathways linked to lineage specification. In particular, we focused here on cationic stretch-activated channels (SACs) because they are known to detect mechanical forces with high sensitivity and broad dynamic range and because they are permeable to Ca 2+ , an important second messenger implicated in cell fate (14,15). We examined the role of SACs in neural stem cells, for which mechanical cues influence specification along the neuronal-glial lineage (8,16,17).…”
mentioning
confidence: 99%
“…Cells of cardiac and vascular tissues, for example, withstand more stress, and their Ca 2+ buffering ability is higher than other cells [28,29]. There are many studies in various matured cells on the patterns of the Ca 2+ oscillations regulated by signaling proteomes [30].…”
Section: Mesenchymal Stem Cells React Differently To Stress Pathologymentioning
confidence: 99%
“…Though low Ca 2+ levels are favorable for all cells in general, higher Ca 2+ levels beyond the threshold are detrimental to MSCs. In general, the physiological role of the Ca 2+ homeostasis largely regulates differentiation, proliferation and cell survival at the site of repair [30]. Studies have revealed the Ca 2+ handling properties of the precursors are similar to the adult differentiated cells as observed in the neuronal precursors compared with differentiated neuronal cells.…”
Section: Mesenchymal Stem Cells React Differently To Stress Pathologymentioning
confidence: 99%